Jacques van Ruiten – Koert van Bekkum (eds.), Violence in the Hebrew Bible . Between Text and Reception (Oudtestamentische Studiën 79; Leiden – Boston, MA: Brill 2020) - Pawlik, Maciej (The Biblical Annals, 2022)
Book Review: Jacques van Ruiten – Koert van Bekkum (eds.), Violence in the Hebrew Bible. Between Text and Reception (Oudtestamentische Studiën 79; Leiden – Boston, MA: Brill 2020). Pp. 438. ISBN 9789004434677